Christmas encounter with a prince - Cudmore, Katrina (Cudmore, Katrina. Royals of Monrosa., 2020)
"Academic Alice seeks refuge in her cousin's London residence to study in blissful peace. However, when the notorious Prince Luis unexpectedly arrives, ruining her solitude, Alice is bewildered by the chemistry they clearly have. He is everything her carefully guarded heart shouldn't want, and yet...as he begins to remove his royal playboy mask, this mysterious prince shows her that Christmas miracles can happen!"--